DOP34 Human MD2 deficiency - an inborn error of immunity predisposing to early onset Inflammatory Bowel Disease. (30th January 2023) - Li, Y; Yu, Z; Schenk, M; Lagovsky, I; Illig, D; Walz, C; Rohlfs, M; Conca, R; Muise, A; Snapper, S; Uhlig, H; Garty, B; et al.
Abstract: Background: Pattern recognition receptors (PRRs) serve as a hub of immune responses to microbes in the gut and play a critical role in maintaining intestinal homeostasis. Toll-like receptor 4 (TLR4) represents an important PRR that can recognize the gram-negative bacterial cell wall component lipopolysaccharide (LPS). Upon binding to LPS, TLR4 forms a multimeric complex with the indispensable co-receptor myeloid differentiation protein 2 (MD2) facilitating selection of TLR4 as cargo for endocytosis and TLR4-mediated activation of downstream signalling. Despite the critical role of TLR4 in innate immunity, no patients with TLR4 or MD2 deficiency have yet been reported. Methods: To investigate potential genetic causes for two related patients presenting with very early onset Inflammatory Bowel Disease (VEO-IBD) and/or pneumonia, we have performed whole exome sequencing (WES). To assess the functional consequences of the identified LY96 (encoding for MD2) variant, we generated a CRISPR/Cas9-mediated knockout (KO) of MD2 or knockin (KI) of the patient mutation in induced pluripotent stem cells (iPSCs) and studied TLR4-mediated signalling, cytokine responses, and bacterial handling in iPSC-derived macrophages. Results: Genetic analysis identified a 3 bp homozygous in-frame deletion in the LY96 gene (NM_015364.5, c.347_349delCAA; p.Thr116del) in our index patients following an autosomal recessive inheritance pattern. Immunoblotting revealed an altered protein expression of overexpressed Flag-tagged mutant MD2 protein due to impaired N-linked glycosylation. Correspondingly, iPSC-derived MD2-deficient macrophages showed an impaired LPS-induced TLR4 endocytosis. As a functional consequence, we could detect reduced NF-κB and MAPK signalling (phosphorylation of NF-κB p65 subunit, ERK1/2, and p38 MAPK) and dysregulated inflammasome activation (IL-1b production and secretion) upon challenge with LPS. Gentamycin protection assays and live cell imaging suggested that MD2-deficient macrophages exhibit an impaired phagocytosis of microbial pathogens. In addition, macrophages with mutant MD2 showed decreased cytokine expression (e.g., IFNB, IL6, IL10, and TNF ) in response to LPS or gram-negative bacteria ( E. coli and Salmonella typhimurium ) but not gram-positive bacteria ( Listeria monocytogenes ). Conclusion: Human MD2 deficiency is an inborn error of immunity that may predispose to VEO-IBD associated with altered TLR4-mediated signalling, cytokine responses, and bacterial handling. The first description of patients with MD2 deficiency provides critical insights on human TLR4/MD2 biology and warrants caution on therapeutics strategies targeting TLR4 signalling.